1996
DOI: 10.1590/s0004-282x1996000300007
|View full text |Cite
|
Sign up to set email alerts
|

Spinal muscular atrophy type II (intermediary) and III (Kugelberg-Welander): evolution of 50 patients with physiotherapy and hydrotherapy in a swimming pool

Abstract: -We added hydrotherapy to 50 patients with spinal muscular atrophy (SMA) who were being treated with individual conventional physiotherapy. Hydrotherapy was performed at an approximate temperature of 30 degrees Celsius, twice a week, for thirty minutes in children and for forty-five minutes in adults during a 2-year period. The outcome derived from this combined modality of treatment was rated according to physiotherapeutic evaluations, the MMT (Manual Muscular Test), and the Barthel Ladder. Patients were reev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 16 publications
1
22
0
4
Order By: Relevance
“…In a study of 50 patients with SMA 2 and 3 followed for 2 years, muscle strength stabilized in all SMA 2 patients and in some SMA 3 patients. All reported improvement on the Barthel Ladder scale, despite progression of existing joint deformities in a majority of patients . A case report described a 3‐year‐old girl with SMA 3 who received aquatic therapy twice‐weekly for 14 weeks, with a corresponding 11% improvement on the Gross Motor Function Measure, along with faster velocity and increased stride length on gait testing …”
Section: Overview Of Exercise Studies In Nmdmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 50 patients with SMA 2 and 3 followed for 2 years, muscle strength stabilized in all SMA 2 patients and in some SMA 3 patients. All reported improvement on the Barthel Ladder scale, despite progression of existing joint deformities in a majority of patients . A case report described a 3‐year‐old girl with SMA 3 who received aquatic therapy twice‐weekly for 14 weeks, with a corresponding 11% improvement on the Gross Motor Function Measure, along with faster velocity and increased stride length on gait testing …”
Section: Overview Of Exercise Studies In Nmdmentioning
confidence: 99%
“…All reported improvement on the Barthel Ladder scale, despite progression of existing joint deformities in a majority of patients. 52 A case report described a 3-year-old girl with SMA 3 who received aquatic therapy twiceweekly for 14 weeks, with a corresponding 11% improvement on the Gross Motor Function Measure, along with faster velocity and increased stride length on gait testing. 53 A minority of patients who survive Poliomyelitis develop sequelae decades after their initial illness, with new weakness, fatigue, and pain.…”
Section: Overview Of Exercise Studies In Nmdmentioning
confidence: 99%
“…The target frequency was fully achieved in one study (Vry 2014), partly achieved in two studies (Lewelt 2015;Madsen 2015), and not reported in six studies (Basoglu 2006;Cunha 1996;Dahl 2004;McCartney 1988;Milner-Brown 1988;Salem 2010). Descriptions of training parameters were incomplete: in four studies with regards to intensity (Basoglu 2006;Cunha 1996;Dahl 2004;Salem 2010), and in three studies with regards to time (Basoglu 2006;McCartney 1988;Milner-Brown 1988). Four studies reported on the occurrence of adverse events (Lewelt 2015;Madsen 2015;McCartney 1988;Vry 2014).…”
Section: Excluded Studiesmentioning
confidence: 98%
“…We excluded nine studies that were not RCTs (see Characteristics of excluded studies). The interventions were strength training alone in four studies (Basoglu 2006;Lewelt 2015;McCartney 1988;Milner-Brown 1988), aerobic exercise training alone in one study (Madsen 2015), aquatic therapy incorporated in a comprehensive rehabilitation program in three studies (Cunha 1996;Dahl 2004;Salem 2010), and a combination of functional strengthening exercises and whole body vibration in one study (Vry 2014). Strength training consisted of concentric resistance training either alone (in McCartney 1988 andMilner-Brown 1988) or in combination with gravity-eliminated movements (in Basoglu 2006 andLewelt 2015).…”
Section: Excluded Studiesmentioning
confidence: 99%
See 1 more Smart Citation